MASSIVE BARITE DEPOSITS AND CARBONATE MINERALIZATION IN THE DERUGIN BASIN, SEA OF OKHOTSK: PRECIPITATION PROCESSES AT COLD SEEP SITES - Greinert J.; Bohrmann G.; Suess E.; Bollwerk S.M.; Derkachev A. (My University, 2002)
An area of massive barite precipitations was studied at a tectonic horst in 1500 m water depth in the Derugin Basin, Sea of Okhotsk. Seafloor observations and dredge samples showed irregular, block-to column-shaped barite build-ups up to 10 m high which were scattered over the seafloor along an observation track 3.5 km long. High methane concentrations in the water column show that methane expulsion and probably carbonate precipitation is a recently active process. Small fields of chemoautotrophic clams (Calyptogena sp., Acharax sp.) at the seafloor provide additional evidence for active fluid venting. The white to yellow barites show a very porous and often layered internal fabric, and are typically covered by dark-brown Mn-rich sediment; electron microprobe spectroscopy measurements of barite sub-samples show a Ba substitution of up to 10.5 mol% of Sr. Rare idiomorphic pyrite crystals (V1%) in the barite fabric imply the presence of H 2 S. This was confirmed by clusters of living chemoautotrophic tube worms (1 mm in diameter) found in pores and channels within the barite. Microscopic examination showed that micritic aragonite and Mg-calcite aggregates or crusts are common authigenic precipitations within the barite fabric. Equivalent micritic carbonates and barite carbonate cemented worm tubes were recovered from sediment cores taken in the vicinity of the barite build-up area. Negative N 13 C values of these carbonates (s 343.5x PDB) indicate methane as major carbon source; N 18 O values between 4.04 and 5.88x PDB correspond to formation temperatures, which are certainly below 5C. One core also contained shells of Calyptogena sp. at different core depths with 14 C-ages ranging from 20 680 to s 49 080 yr. Pore water analyses revealed that fluids also contain high amounts of Ba; they also show decreasing SO 2À 4 concentrations and a parallel increase of H 2 S with depth. Additionally, S and O isotope data of barite sulfate (N 34 S: 21.0^38.6x CDT; N 18 O: 9.0^17.6x SMOW) strongly point to biological sulfate reduction processes. The isotope ranges of both S and O can be exclusively explained as the result of a mixture of residual sulfate after a biological sulfate reduction and isotopic fractionation with 'normal' seawater sulfate. While massive barite deposits are commonly assumed to be of hydrothermal origin, the assemblage of cheomautotrophic clams, methane-derived 0012-821X / 02 / $ ^ see front matter ß 2002 Elsevier Science B.V. All rights reserved. PII: S 0 0 1 2 -8 2 1 X (0 2) 0 0 8 3 0 -0 (J. Greinert), sbollwerk@geomar.de (S.M. Bollwerk), paci¢c@online.marine.su (A. Derkachev), gbohrmann@geomar.de (G. Bohrmann), esuess@geomar.de (E. Suess). EPSL 6349 24-9-02 Cyaan Magenta Geel Zwart Earth and Planetary Science Letters 203 (2002) 165^180 www.elsevier.com/locate/epsl carbonates, and non-thermally equilibrated barite sulfate strongly implies that these barites have formed at ambient bottom water temperatures and form the features of a Giant Cold Seep setting that has been active for at least 49 000 yr.